1997
DOI: 10.1099/0022-1317-78-8-2009
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of rhesus cytomegalovirus glycoprotein B.

Abstract: Pathogenicity of human cytomegalovirus (HCMV) correlates with the immune status of infected individuals. In fully immunocompetent individuals, host antiviral immune responses contain virus replication. In contrast, HCMV can be a serious cause of morbidity and mortality in individuals without an intact immune system (Ho, 1991). Greater understanding of both host antiviral immune responses and mechanisms of viral pathogenesis is required to design strategies which effectively limit HCMV disease. Infection of rhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 16 publications
3
16
0
Order By: Relevance
“…For example, the gBs of MCMV and RCMV have 45 and 60% overall homology, respectively, to HCMV gB (33,34,46). Locally, there are regions of these gBs having much greater identity with the corresponding region of HCMV gB.…”
Section: Vol 78 2004 Small Molecule Inhibitor Of Hcmv Fusion 1295mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the gBs of MCMV and RCMV have 45 and 60% overall homology, respectively, to HCMV gB (33,34,46). Locally, there are regions of these gBs having much greater identity with the corresponding region of HCMV gB.…”
Section: Vol 78 2004 Small Molecule Inhibitor Of Hcmv Fusion 1295mentioning
confidence: 99%
“…gB-based fusion assays with either antibodies mapping to gp55, or various gp55 mutants, have indicated that this region plays an essential role in penetration (4,41,53,54). Resistance-conferring mutations G733S and F751L are within regions of high homology with gB of MCMV and RCMV; in both of these betaherpesvirus examples, the wild-type HCMV amino acid is conserved (33,34,46). The fact that CFI02 does not inhibit MCMV or RCMV indicates that the gB-CFI02 interaction requires more than just a single contact or interaction domain.…”
Section: Vol 78 2004 Small Molecule Inhibitor Of Hcmv Fusion 1295mentioning
confidence: 99%
“…Primer and probe sequences were designed to the glycoprotein B gene (UL55) of RhCMV (accession no. U41526) (12) by using the Primer Express program (version 1.0). The forward and reverse primer sequences were 5Ј-TGC GTA CTA TGG AAG AGA CAA TGC-3Ј and 5Ј-ACA TCT GGC CGT TCA AAA AAA C-3Ј, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…gB, a major target of anti-HCMV antibodies, is also well conserved in RhCMV. The cloned RhCMV gB is proteolytically processed similarly to HCMV gB, portions of RhCMV gB cross-react with anti-HCMV gB antibodies, and RhCMV gB antibodies can be detected during RhCMV infection [56,57]. Phosphoprotein 65 (pp65) is another dominant target for the immune response to HCMV.…”
Section: Functional Characterizations Of Rhcmv Proteinsmentioning
confidence: 99%